An efficiency measurement of Islamic charitable non profit organization: a data envelopment analysis application - Ibrahim, Dahlia; Mohamed Isa, Zuraidah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
Giving is customary in the community, regardless of one's religious or secular motivations. Most donors take the non-profit organization (NPO)'s effectiveness in handling their money into account before making a contribution. To put it plainly, donors are curious about how well the nonprofit distributes their funds to the designated beneficiaries. An NPO is by definition a charity that raises funds and uses them to advance the welfare of society. Its major goal is to raise money and use it for social benefit, acting as a mediator between the donors and the community. On the other hand, an NPO functions in a manner akin to that of other charitable institutions. Its role is gathering public donations and allocating them for the ummah's benefit. Unlike other charitable organizations, the Islamic non-profit organization operates according to the shariah principle.